Influence of financialization on the business activity of non-financial enterprises in Poland - Rydzewska, Alina (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: Financialization is connected with the phenomenon of dominance of the financial sphere in relation to the real sphere. Financialization, when applied to non-financial entities, means the increase of importance of financial motives in the decision-making processes of enterprises. Changes result from transformations of the system of economic incentives and development patterns, both in the economy and among economic entities, which are focused on fast earning. Enterprises for that purpose, they use leverage and financial instruments to generate profit, limiting the operational and investment activity. Aim: The aim of this paper is to examine if the processes of financialization have affected the activities of non-financial enterprises operating in Poland based on a multifaceted analysis of the financialization of enterprises: from the point of view of investment activities (assets), sources of external financing (liabilities), income and management. Moreover, an attempt was made to answer the question if these processes apply equally to particular industries and enterprises according to their size. Results: The conducted research showed that non-financial enterprises operating in Poland do not show signs of financialization of their activities. There is a noticeable upward trend in active and passive financial instruments of the balance sheet total. However, it does not translate into an increase in financial income. Research related to factors affecting ROE as a measure of shareholder value assessment, showed that it is determined by operating performance. In addition, the research showed that there were no statistically significant differences in the financialization of operations between large companies and the SME sector. With regard to sectors, the research indicated that there were sectors that differed from the others. In terms of the degree of financialization of assets, liabilities and income, it is sector L — “Real estate activities”.